Thymosin‐β4 is a determinant of drug sensitivity for Fenretinide and Vorinostat combination therapy in neuroblastoma - Cheung, Belamy B. (Mol Oncol, 2015)
Retinoids are an important component of neuroblastoma therapy at the stage of minimal residual disease, yet 40–50% of patients treated with 13‐cis‐retinoic acid (13‐cis‐RA) still relapse, indicating the need for more effective retinoid therapy. Vorinostat, or Suberoylanilide hydroxamic acid (SAHA), is a potent inhibitor of histone deacetylase (HDAC) classes I & II and has antitumor activity in vitro and in vivo. Fenretinide (4‐HPR) is a synthetic retinoid which acts on cancer cells through both nuclear retinoid receptor and non‐receptor mechanisms. In this study, we found that the combination of 4‐HPR + SAHA exhibited potent cytotoxic effects on neuroblastoma cells, much more effective than 13‐cis‐RA + SAHA. The 4‐HPR + SAHA combination induced caspase‐dependent apoptosis through activation of caspase 3, reduced colony formation and cell migration in vitro, and tumorigenicity in vivo. The 4‐HPR and SAHA combination significantly increased mRNA expression of thymosin‐beta‐4 (Tβ4) and decreased mRNA expression of retinoic acid receptor α (RARα). Importantly, the up‐regulation of Tβ4 and down‐regulation of RARα were both necessary for the 4‐HPR + SAHA cytotoxic effect on neuroblastoma cells. Moreover, Tβ4 knockdown in neuroblastoma cells increased cell migration and blocked the effect of 4‐HPR + SAHA on cell migration and focal adhesion formation. In primary human neuroblastoma tumor tissues, low expression of Tβ4 was associated with metastatic disease and predicted poor patient prognosis. Our findings demonstrate that Tβ4 is a novel therapeutic target in neuroblastoma, and that 4‐HPR + SAHA is a potential therapy for the disease.